Web Information Systems Engineering - WISE 2012 13th International Conference, Paphos, Cyprus, November 28-30, 2012. Proceedings - Wang, X. Sean.; Cruz, Isabel; Delis, Alex.; Huang, Guangyan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 13th International Conference on Web Information Systems Engineering, WISE 2012, held in Paphos, Cyprus, in November 2012. The 44 full papers, 13 short papers, 9 demonstrations papers and 9 (3z(Bchallenge(3y (Bpapers were carefully reviewed and selected from 194 submissions. The papers cover various topics in the field of Web Information Systems Engineering.s
Improving the Performance of Pipelined Query Processing with Skipping -- Learning to Find Comparable Entities on the Web -- Sentiment Analysis by Augmenting Expectation Maximisation with Lexical Knowledge -- Event-Driven Ontology Updating -- BiCWS: Mining Cognitive Differences from Bilingual Web Search Results -- Towards a User-Centric Social Approach to Web Services Composition, Execution, and Monitoring.
Keywords: Computer science; Software engineering; Information systems; Data mining; Information storage and retrieval systems; Computer Science; Information Systems Applications (incl. Internet).; Information Systems and Communication Service; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; Software Engineering; Data Mining and Knowledge Discovery